Hopeless Cases: In Defence of Compensating Litigants at the Advocate's Expense - Webb, Duncan (Victoria University of Wellington Law Review, 1999)
The dividing line between novel litigation and cases which are an abuse of process and a waste of time can be a difficult one to draw. Some would argue that the tension between these two public policies is reason enough not to award costs against an advocate bringing or defending "hopeless" causes. The author, however, is of the view that the jurisdiction to award such costs is justified in the interests of protecting clients and maintaining professional standards. An analysis of the case law reveals that the power is used sparingly and, if there is any doubt, the court will favour the advocate.